(3GJLGgGJ MOjKI aj GdJfejIs - (3YWjI(B, (3YHO GdbGOQ eMeO YHO GdbGOQs ((3GdbGgQIs (3GdOGQ GdLGeYjIs, 2003)
(3eaghe Gdfeh hGdJfejI(B- (3JfejW GdJfejI(B- (3SjGSGJ hCSGdjH GdJfejI GdHTQjI(B- (3JMdjd GdBKGQ GdJfehjI ddNUNUI(B- (3OhQ GdOhdI aj Xd EbJUGOjGJ GdShb(B- (3GdJZjQGJ GdEbJUGOjI GdYGdejI hCKQgG Ydi GdJfejIs
Keywords: (3GdJfejI GdEbJUGOjIs